PEMANFAATAN ANTROPOMETRI GIZI UNTUK PENENTUAN SASARAN PROGRAM PENANGGULANGAN KEMISKINAN - Herman Sudirman; Syarifudin Latinulu; Sri Prihartini; Vita Kartika (Persagi, 2000)
THE USE OF NUTRITIONAL ANTHROPOMETRICS DATA FOR TARGETING OF POVERTY ALLEVIATION PROGRAM.Background: In limited fund situation and increased of poor population, the selection of the targets of poverty alleviation program becomes very important The precise targeting means save the fund and help the needy household. Based on the experiences in poverty alleviation program generally the weaknesses are selecting the targets. Nutritional anthropometrics data are available but they are not optimally use to support the poverty alleviation program. Studies on anthropometries data and their correlation with social-economic data, recipient from other poverty alleviation program can help to select the targets.Objective: To study the agreement of nutritional indicator with other indcator to select targets for poverty alleviation program.Method: Research was conducted at 4 districts in West Java. At each district was chosen 2 sub districts with the highest proportion of poverty household and with the same method in each sub district 1 village were chosen. In each village were choose randomly 80 families. The entire household member was measure on their weight and height. Other data was collect by interview and observation. Agreement test was performed to test on the targeting done by the poverty alleviation program such as Social Safety Net program with nutritional anthropometrics indicator.Conclusions: 1. Based on the occupation, education and income estimation of household head, generally household samples were categorized as poor and deserve to be the target of the program. 2. Data of recipient from religious organization until the end of the research cannot be collected so it cannot be analyze. 3. Body Mass Index (BMI) of household head and wife less than 18,5 kg/m2 has high agreement for targeting. 4. Anthropometrics indcator of children under 5 years using cut off point <-2 Z score and <-3 Z score have high agreement to targeting, except for weight-for-height using cut off point <-3 Z score.Key Words: poverty indicator, anthropometrics, agreement of indicator